Pharmacology of some oral penicillins in the newborn infant. Issue 3 (March 1975) - Cohen, M D; Raeburn, J A; Devine, J; Kirkwood, J; Elliott, B; Cockburn, F; Forfar, J O
Abstract : Serum and urine concentrations of ampicillin, amoxycillin, and flucloxacillin achieved after oral administration have been measured in 27 newborn infants. Compared with adults and children, newborn infants show a delay in achieving adequate blood concentrations, presumably due to delayed absorption. However most infants achieve therapeutic concentrations in the serum. Infected newborn infants should be given these antibiotics by intramuscular injection for the first dose, but thereafter oral therapy (25 mg/lg every 6 hours begun concomitantly) should be satisfactory. The better absorption of amoxycillin compared with ampicillin reported in adults has not been confirmed in the newborn infant.